PENGEMBANGAN BAHAN AJAR MATEMATIKA BERBASIS PENEMUAN TERBIMBING PADA POKOK BAHASAN STATISTIKA KELAS IX SMP/MTS - Nismalasari Jufri; Baharuddin; Fitriani Nur; A. Sriyanti; M. Yusuf Tahir (Al asma : Journal of Islamic Education, 2022)
The purpose of this study is to produce guided discovery-based teaching materials on the subject of statistics. The development model used is the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The quality of the learning developed is seen from the aspects of validity, practicality, and effectiveness. Aspects of validity based on validation scores by two validators, aspects of practicality based on student responses, and aspects of effectiveness based on student learning outcomes after using teaching materials. Based on the results of validation by two validators obtained very valid criteria. The value of practicality based on the responses of students is obtained that this media is very practical to be used at the large-scale trial stage. Furthermore, the value of practicality is based on the responses of students in stage II with very practical criteria. Finally, the effectiveness test obtained based on the student learning outcomes test, it is known that the average learning outcomes test has met the KKM value, which means that learning material are effectively used in the learning process.